Effect of temperature on composition evolution of oxide film on Al–Mg–Sc alloy. (September 2022) - Wu, Mingjin; Ye, Pengcheng; Wu, Feifei; Long, Mengjun; Jiang, Feng
Abstract: The effects of temperature on the component of oxide film on oxidized Al–Mg-Sc alloy surface and the microstructure of Al substrate near the interface were investigated and the relationship between composition change and microstructure evolution was discussed. Results suggested that the morphology of oxide scale evolved from the amorphous oxide layer with dense and uniform structure to the oxide layer with loose structure composed of MgO cluster particles. At 300 °C, the main components of oxide film were Al2 O3 and MgO. With the oxidation temperature increasing, MgO gradually made up a major part of the oxide film. When the oxidation temperature reached 500 °C, the major components of the oxide film were MgO and MgAl2 O4 and the generation of MgAl2 O4 dominated over MgO. With the temperature increasing, the crystal orientation of Al substrate near the interface changed from <101> to <111>, and the transformation of crystal orientation favoured the diffusion of Mg atoms. Meanwhile, the content of high angle grain boundaries (HAGBs) increased significantly, and there were many regions with poor atom matching at the HAGBs, where Mg atoms accelerated the migration to the oxidized Al–Mg-Sc alloy surface to participate in chemical reactions to finally form MgAl2 O4 at the interface. Highlights: The composition evolution with film depth on alloy surface were determined. The microstructure evolution of the Al substrate near the interface was analyzed. The relationship between crystal orientation and composition evolution was explored.